Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan - Bonita Revana Indriani; Muhammad Julda Alhafiz; Rafi Eka Nugraha; Dewi Sri Woelandari Giningroem (STIKes Ibnu Sina Ajibarang, 2024)
Amidst a progressively intricate and constantly evolving corporate landscape, the performance of employees holds significant significance in attaining organisational triumph. The correlation between leadership style and the degree of motivation in the work environment has a substantial impact on the quality and productivity of employees. The objective of this study is to ascertain the impact of leadership style and motivation on employee performance in the workplace. For this study, we employed a thorough literature review as our research methodology, gathering pertinent and current information from relevant scholarly articles, journals, and books. Empirical evidence demonstrates that the manner in which leaders lead and the level of motivation present in the work setting exert a substantial impact on enhancing employee performance. This knowledge provides a valuable foundation for the development of more efficient leadership methods and motivating programs that can be implemented in the workplace.